Hydrogen Peroxide Responsive Iron–Based Nanoplatform for Multimodal Imaging–Guided Cancer Therapy. Issue 4 (20th December 2018) - Wang, Peng; Shi, Yunhao; Zhang, Shichao; Huang, Xiaoyu; Zhang, Jiaojiao; Zhang, Yewei; Si, Weili; Dong, Xiaochen
Abstract: Cancer multimodal phototherapy triggered by hydrogen peroxide has attracted widespread attention as a dominating strategy to increase phototherapeutic efficiency. Herein, a hydrogen peroxide responsive iron oxide nanoplatform, with the diameter of about 50 nm, is fabricated to intracellularly trigger the Fenton reaction and achieve synergistic photodynamic therapy and photothermal therapy. The nanoplatform based on iron oxide nanoparticles is decorated with indocyanine green (ICG, photosensitizer) and hyaluronic acid (HA, targeting molecular) through electrostatic interaction, thus the as‐prepared nanoplatform (IONPs‐ICG‐HA) exhibits excellent active targeting ability and biocompatibility. More importantly, it can effectively utilize the intratumoral overproduced hydrogen peroxide to generate reactive oxygen species for cancer cell killing via intracellular Fenton reactions. In vitro and in vivo experiments reveal that the IONPs‐ICG‐HA nanocomposites realize effective photoacoustic/photothermal/fluorescence imaging–guided phototherapy, leading to promising hydrogen peroxide responsive cancer theranostics. Abstract : A hydrogen peroxide stimuli‐responsive iron–based nanoplatform for cancer photodynamic/photothermal synergistic therapy is developed monitored by multiple bioimaging.